Investigating the public transport system in Cape Town with reference to special needs passengers - Ribbonaar, Deidre (Cape Peninsula University of Technology, 2013)
Thesis (MTech (Town and Regional Planning))--Cape Peninsula University of Technology, 2005 === Inadequacies of the current public transport system cause an inconvenience for "normal able-bodied" passengers; however, it arguably isolates Special Needs Passengers (SNPs) from employment opportunities, recreational and educational opportunities. This research study focuses on what one might term mobility-handicapped persons who find it difficult to move around, or to hear and see. The term SNP or mobilityhandicapped persons encompasses more than just disabled persons. It includes customers laden with shopping bags, pregnant women, or someone with a broken leg, inter alia. The public transport system should enable persons with disabilities to experience the most optimal level of independence. It is crucial to have an accessible public transport system, because this is the first step in achieving independence for many SNP's. At present the system does not even satisfy the needs of able-bodied persons. How then is it supposed to respond to Special Needs Passengers? The public transport system can be divided into 4 categories namely, Infrastructure, Shared Road and Pedestrian Environment, Information and Vehicles. At present, these components of the system do not function efficiently. This research study was undertaken from three main perspectives in regard to the City of Cape Town: • The performance of the public transport system with reference to SNPs, • The performance of the city in terms of it's urban qualities and SNPs, and • The adequacy of the existing legal provisions and policy frameworks with reference to SNPs.